2005
DOI: 10.1007/s00540-005-0341-1
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion and glucose utilization are impaired under general anesthesia with sevoflurane as well as isoflurane in a concentration-independent manner

Abstract: Sevoflurane anesthesia impairs glucose tolerance to the same degree as does isoflurane anesthesia. Glucose intolerance during sevoflurane or isoflurane anesthesia is independent of agent and dosage up to 1.5 MAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 14 publications
9
63
4
2
Order By: Relevance
“…Anaesthesia increases stress signals through catecholamines and cortisol excretion or may influence glucose homeostasis via insulin release. (Tanaka et al, 2005;Zuurbier et al, 2008). Studies on mice and rats have confirmed that a decrease in body temperature, as a result of anaesthesia, may further increase glucose levels (Tabata et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Anaesthesia increases stress signals through catecholamines and cortisol excretion or may influence glucose homeostasis via insulin release. (Tanaka et al, 2005;Zuurbier et al, 2008). Studies on mice and rats have confirmed that a decrease in body temperature, as a result of anaesthesia, may further increase glucose levels (Tabata et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Volatile anesthetics, such as sevoflurane, attenuate insulin secretion by activating Table 6. Changes in blood glucose levels during insulin tolerance tests in groups S-ITT, SL-ITT, and P-ITT adenosine triphosphate-sensitive potassium channels in β-islet cells (2)(3)(4)(5). We previously found that propofol anesthesia enhances insulin secretion in rats (6,7).…”
Section: Discussionmentioning
confidence: 97%
“…Volatile anesthetics, such as sevoflurane, activate adenosine triphosphatesensitive potassium channels in β-islet cells, resulting in attenuated insulin secretion (2)(3)(4)(5). Although the precise mechanisms have not been elucidated, insulin secretion is significantly enhanced in rats under propofol anesthesia (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Anesthesia in general alters glycemic homeostasis, and inhalation anesthetics in particular are known to diminish glucose-stimulated insulin secretion (24). If combined with invasive experimental techniques, these basal premises for utilization of step hot-GINF HEC might additionally be altered by elevated counterregulatory hormones due to surgical instrumentation.…”
Section: Discussionmentioning
confidence: 99%